2017
DOI: 10.1016/j.agee.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Shade trees have limited benefits for soil fertility in cocoa agroforests

Abstract: A B S T R A C TAgroforestry is often promoted as a sustainable agricultural practice that can ameliorate causes of declining yields, such as soil degradation. However, despite the often-stated potential of agroforestry, quantitative data on the benefits of shade trees are limited to relatively few cropping systems, particularly maize and coffee. Furthermore, agroforests are not cost-free and the benefits of agroforests might not be sufficient to outweigh these costs in all cropping systems or environments. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 47 publications
(72 reference statements)
2
51
0
1
Order By: Relevance
“…Both the cocoa yield and the incident light were a logistic function of the planting distance from the shade trees. Our results were also in line with those of Blaser et al (2017) who, in Ghana, showed that cocoa growth was lower under shade trees and decreased with increasing shade-tree cover, as it was also observed for cocoa yield. The correlation between the unproductive adult cocoa tree rate on one hand, and the density of associated trees or the number of associated species on the other hand (Table 2D) confirmed that competition for water, light, and nutrients was a factor limiting yield build-up in cocoa stands (Besse 1972;Lachenaud and Mossu 1985).…”
Section: Factors That Limit Yield and Yield Componentssupporting
confidence: 81%
“…Both the cocoa yield and the incident light were a logistic function of the planting distance from the shade trees. Our results were also in line with those of Blaser et al (2017) who, in Ghana, showed that cocoa growth was lower under shade trees and decreased with increasing shade-tree cover, as it was also observed for cocoa yield. The correlation between the unproductive adult cocoa tree rate on one hand, and the density of associated trees or the number of associated species on the other hand (Table 2D) confirmed that competition for water, light, and nutrients was a factor limiting yield build-up in cocoa stands (Besse 1972;Lachenaud and Mossu 1985).…”
Section: Factors That Limit Yield and Yield Componentssupporting
confidence: 81%
“…Shade tree management in cocoa plantation has been discussed for decades regarding their benefits and disadvantages for cAFS (Andres et al, 2016;Blaser et al, 2017;Niether et al, 2019;Sanchez, 1995). The microclimatic regulation introduced by shading decreases diseases' outbreaks, which are known to hamper both cocoa yield and sustainability (Andres et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Shade tree effects on cocoa yield, nutritional status and soil fertility has been studied both at the community (Blaser, Oppong, Yeboah, & Six, ; Niether, Schneidewind, Fuchs, Schneider, & Armengot, ) and at the species level (Isaac, Timmer, & Quashie‐Sam, ; Wartenberg et al, ). Depending on the study, observed effects are explained by a variety of individual or community properties such as above‐ground biomass (Isaac, Timmer, et al, ; Niether et al, ; Wartenberg et al, ), leaf biomass nutrient concentration (Isaac, Timmer, et al, ; Wartenberg et al, ) or canopy architecture and/or cover (Blaser et al, ; Isaac, Timmer, et al, ; Wartenberg et al, ). Nonetheless, to our knowledge, there is no study considering the specific relationships between shade tree functional traits and agroecosystem functioning in cAFS.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of native forest systems to cocoa cultivation frequently depletes SOM [24] as a result of physical disturbance and lack of replenishment of organic matter exported from the system with each crop [25]. Such decline in SOM has been linked to declines in cocoa productivity and bean quality with time since land conversion to cocoa farms [26].…”
Section: Low Value Applications Of Cph Fertiliser and Soil Organic Mamentioning
confidence: 99%